Determination of total phenolic and flavonoid contents, antioxidant and antibacterial potential of the bark extracts of Syzygium guineense (Wild.) DC. - Engeda Dessalegn; Mengisteab Mathewos; Hiwot Gebremeskel; Nigatu Tuasha (BMC Complementary Medicine and Therapies)
Abstract Background Syzygium guineense (Wild.) DC. is a wild indigenous tree widely used as a traditional medicine for various human ailments in Ethiopia. The purpose of this study was to quantify total phenolic (TPC) and total flavonoid (TFC) contents and determine the antioxidant and antibacterial activities of various solvent extracts of the bark of the plant. Methods The TPC and TFC were determined using Folin-Ciocalteu and aluminum chloride methods, respectively. The 2, 2-diphenyl-1–picrylhydrazyl (DPPH) scavenging, ferric-reducing power, and total antioxidant capacity assays were used to evaluate the antioxidant activities. Antibacterial properties were determined using the disc-diffusion and broth dilution assays. Results The ethanol extract of the bark was found to have high TPC (37.80 ± 3.70 mgGAE/g) and TFC (19.22 ± 1.44 mgQE/g). Similarly, the ethanol extract showed stronger DPPH scavenging activity (EC50 = 5.62 μg/mL). The ferric-reducing power and total antioxidant capacity were also strong (163.08±11.67 mgAAE/g and 143.72±2.86 mgBHTE/g of dried extract of 1 mg/mL, respectively). The lowest MIC was observed in acetone extract against S. aureus (1.56 mg/mL) and in ethanol extract against K. pneumoniae (1.56 mg/mL). Conclusion The ethanol extract of the bark of S. guineense possesses high TPC and TFC. In addition, it showed strong ferric-reducing power and total antioxidant capacity, asserting high antioxidant content. The extracts have shown antibacterial activities against both Gram-positive (S. aureus) and Gram-negative bacterial species. Thus, further in-depth investigations may warrant the isolation of powerful antioxidants and potent antimicrobial agents from the plant.